Assessing the impacts of future urban expansion on multiple ecosystem services in the transnational area of Changbai Mountain - Chen, Ruikang; Zhang, Da; Nan, Ying; Feng, Hengdong; Geng, Xin (Frontiers in Earth Science, 2023)
Introduction: An assessment of the potential impacts of future urban expansion on multiple ecosystem services (ESs) represents an essential contribution to the sustainable development of the transnational area of Changbai Mountain (TACM). However, the potential ES losses attributed to future urban expansion have been assessed in few studies. Methods: In this study, we evaluated the potential ES losses attributable to urban expansion in the TACM over the period from 2015 to 2050. To achieve this objective, we initially quantified multiple ESs (namely, food production (FP), carbon storage (CS), water retention (WR), and air purification (AP)) based on 1992 data, and subsequently simulated urban expansion from 2015 to 2050 by coupling Shared Socioeconomic Pathways scenarios (SSPs) with the zoned Land Use Scenario Dynamics-urban model. Finally, the potential impacts of future urban expansion on ESs were evaluated on multiple scales. Results: The results indicated that during the period from 2015 to 2050, the extent of urban land will grow by between 157.59 and 517.77 km2, resulting in FP, CS, WR, and AP losses of 193.76–684.39 thousand tons, 1.47–5.24 million tons, 8.74–30.00 million tons, and 0.34–1.18 thousand tons, respectively. Discussion: The subregion falling within the Democratic People’s Republic of Korea (DPRK) will experience the most severe future losses of ESs, with losses of FP, CS, WR, and AP being 1.06–3.77-fold, 1.15–3.46-fold, 1.10–3.54-fold, and 1.08–3.21-fold higher, respectively than those that occurred in this subregion the period of 1992–2015. Specifically, the encroachment of new urban land onto cropland and woodland will be the main contributing factor in these future declines in ESs. Furthermore, the reductions in ESs attributable to urban expansion in this subregion will have serious effects on human wellbeing. By 2050, the loss of FP will affect approximately 9.58%–30.00% of the population. Moreover, among the residents of this subregion, the loss of AP will contribute to the need for additional expenditures of 6.63–19.81 million euros on air purification measures. On the basis of these findings, we suggest that effective policies and regulations should be implemented to promote the sustainable development of the TACM.